2011
DOI: 10.1016/j.actamat.2010.10.064
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical investigation of environmental media on very-high-cycle fatigue behavior for a structural steel

Abstract: Rotary bending fatigue tests were performed in laboratory air and 3.5% NaCl aqueous solution to investigate the influence of environmental media on fatigue properties of a structural steel in high-cycle and very-high-cycle fatigue regimes. The results show that the fatigue strength of the structural steel in 3.5% NaCl solution is remarkably degraded compared with the case tested in laboratory air. The fracture surfaces of specimens tested in different environments were examined to reveal the fatigue crack init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
76
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 27 publications
0
76
0
Order By: Relevance
“…In fact, there is a need for many engineering structures to endure long period of cyclic loading up to 10 10 cycles, such as aircrafts, automobiles, ship, railway, etc. [5]. Obviously, it is an important topic to clarify the behavior and mechanism of VHCF failures.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there is a need for many engineering structures to endure long period of cyclic loading up to 10 10 cycles, such as aircrafts, automobiles, ship, railway, etc. [5]. Obviously, it is an important topic to clarify the behavior and mechanism of VHCF failures.…”
Section: Introductionmentioning
confidence: 99%
“…Miller et al [6] also discussed the fatigue limit and methods for overcoming it. Therefore, some high strength CrMo steels with both good HCF performance and good corrosion fatigue performance [8,16,17] have been reported recently. Sakai et al [18] and Huang et al [19] previously reported on the HCF or VHCF issues of high carbon chromium bearing steel and low alloy chromium steel, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, the process of subsurface crack initiation and propagation is still not clear and there are few theoretical models developed to analyze the different crack initiation process [8,9,13,20]. Additionally, although there have been many studies on the factors those may affect VHCF propensity of high strength steels, such as environmental medium [14][15][16], loading frequency [17,18], microstructure state [19][20][21], etc. [5,8,12], the influence of notch effect has not been fully understood.…”
Section: Introductionmentioning
confidence: 99%